2019
DOI: 10.3390/su11205638
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Properties of Rapeseed Oil Enriched with Oils Characterized by High Content of α-linolenic Acid

Abstract: Functional foods include cold-pressed oils, which are a rich source of antioxidants and bioactive n-3 and n-6 polyunsaturated fatty acids. The aim of this study was to assess the quality of rapeseed oils supplemented with Spanish sage and cress oils. Seven oil mixtures consisting of 70% of rapeseed oil and 30% of sage and/or cress oil were prepared for the analyses. The oil mixtures were analyzed to determine their acid value, peroxide value, oxidative stability, and fatty acid composition. In terms of the aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…These vegetable oils contain large amounts of n-6 PUFAs and wide n-6:n-3 ratios; only rapeseed oil making an exception comprising higher amounts of n-3 PUFAs. The content of LA (C18:2 n-6) and ALA (C18:3 n-3) in rapeseed oil typically amounts to 20% and 10%, respectively, while about 8% FAs are saturated and 55% are monounsaturated oleic acid [68]. By contrast, sunflower oil is extremely rich in n-6 PUFAs, containing about 15% saturated and 85% unsaturated FAs, including monounsaturated FAs (14-43% oleic acid C18:1 n-9) and PUFAs (44-75% LA C18:3 n-3) [69] (Akkaya, 2018).…”
Section: Lipids and Bioactive Fa In Milk Replacers And Solid Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…These vegetable oils contain large amounts of n-6 PUFAs and wide n-6:n-3 ratios; only rapeseed oil making an exception comprising higher amounts of n-3 PUFAs. The content of LA (C18:2 n-6) and ALA (C18:3 n-3) in rapeseed oil typically amounts to 20% and 10%, respectively, while about 8% FAs are saturated and 55% are monounsaturated oleic acid [68]. By contrast, sunflower oil is extremely rich in n-6 PUFAs, containing about 15% saturated and 85% unsaturated FAs, including monounsaturated FAs (14-43% oleic acid C18:1 n-9) and PUFAs (44-75% LA C18:3 n-3) [69] (Akkaya, 2018).…”
Section: Lipids and Bioactive Fa In Milk Replacers And Solid Dietsmentioning
confidence: 99%
“…By contrast, sunflower oil is extremely rich in n-6 PUFAs, containing about 15% saturated and 85% unsaturated FAs, including monounsaturated FAs (14-43% oleic acid C18:1 n-9) and PUFAs (44-75% LA C18:3 n-3) [69] (Akkaya, 2018). Rapeseed oil exhibits good oxidative stability, which is higher than that of soybean and sunflower oils [68]. By having a lower oxidative stability and due to their lower availability and higher price, n-3 PUFA rich oils, such as linseed or hempseed oil, have been less used in (pre-)starter diets.…”
Section: Lipids and Bioactive Fa In Milk Replacers And Solid Dietsmentioning
confidence: 99%
“…They should be present in appropriate proportions. In a high-quality product, the MUFA:PUFA ratio should be 1:2-5 [31]. Most niche oils meet this criterion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These compounds have primarily antioxidant activity. 70 Lavender oil Phytochemical studies of extract of lavender oil revealed that the major constituents are endoborneol, 1,8-cineole and compounds those are found in minor quantity are limonene, terpinen-4-ol, -pinene, camphene, p-cymene and cryptone. 71 The studies have been performed for various therapeutic and pharmacological activities such as anticonvulsant, anxiolytic, antiinflammatory and antioxidant.…”
Section: Rapeseed Oilmentioning
confidence: 99%